2012
DOI: 10.1111/j.1600-0625.2012.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Periostin, a matricellular protein, accelerates cutaneous wound repair by activating dermal fibroblasts

Abstract: Cutaneous wound repair is a highly ordered and wellcoordinated process involving various cell lineages and many molecular effectors. Cell-matrix interactions through integrin molecules provide key signals important for wound repair. Periostin is a matricellular protein that may provide signals important during tissue development and remodelling by interacting with several integrin molecules, via the phosphatidylinositol 3-kinase ⁄ Akt and MAP kinase pathways. In this study, we examined the role of periostin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 55 publications
7
109
3
Order By: Relevance
“…The direct or indirect production or promotion of TGF-beta could be incriminated for Col 1a2 transcription by competent cells (17). However, other factors that may induce profibrotic mediators by intermediate cell types could also be considered (5,(18)(19)(20). Naturally, because of the central role of macrophages in wound healing biology, these hypotheses are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The direct or indirect production or promotion of TGF-beta could be incriminated for Col 1a2 transcription by competent cells (17). However, other factors that may induce profibrotic mediators by intermediate cell types could also be considered (5,(18)(19)(20). Naturally, because of the central role of macrophages in wound healing biology, these hypotheses are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…4V) (Nystrom et al 2013); and periostin (POSTN) and phospholipase C-eta-2 protein (PLCH2), which are mainly expressed in dermal fibroblasts ( Fig. 4X-4Y) (Ontsuka et al 2012). …”
Section: Proteins Expressed In Melanocytes Langerhans Cells and Fibrmentioning
confidence: 99%
“…Periostin induces proliferation of cardiomyocytes, modulating the healing process of myocardial infarction (13,14). We and others have recently shown that periostin has another physiological role in cutaneous wound repair (15)(16)(17). Furthermore, periostin is involved in the development of various tumors via the integrin/PI3K/Akt pathway (10).…”
Section: Introductionmentioning
confidence: 99%